Primary hepatic carcinosarcoma: a case report with insights from retrospective analysis of clinical characteristics and prognostic factors - Zhao, Zonglei; Wang, Tao; Sun, Zhexuan; Cao, Xuefeng; Zhang, Xingyuan (Frontiers in Medicine, 2025)
Primary hepatic carcinosarcoma (HCS) is an extremely rare malignant tumor with carcinomatous and sarcomatous elements. Few reported cases of HCS exist, especially with sufficient records to describe imaging and pathological features, making the diagnosis, treatment, and prognosis of HCS a significant challenge for physicians. Here, we report a case of HCS with spontaneous rupture as the initial symptom in a 77-year-old elderly male who was admitted with right upper abdominal pain for 8 days. The computed tomography enhancement scan revealed one intrahepatic enhancement with mixed density and a massive, enhanced shadow located mainly outside the liver. We performed a hepatectomy of segment 4 through a laparotomy. The postoperative pathology results demonstrated HCS. The patient recovered smoothly and was discharged after surgery. However, the patient experienced a recurrence and died 5 months after surgery. This case underscores the importance of identifying high-risk populations and personalized treatment strategies in HCS cases.